GIS-material for the archaeological project: Cultural layers and remnants of iron working by the Smedby burial ground - Foot and cycle path between Brånnestad and Rambodal - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
Due to construction of a new walk and bicycle path between Brånnestad and Rambodal, the Swedish National Heritage Board's Contract Archaeology Service, UV Öst, performed an excavation in the "Skålsvampen" city block in Smedby, formerly in S:t Johannes parish, in the city of Norrköping, Östergötland county. A previous field evaluation had noted prehistoric settlement remains along the planned trail. The excavation was performed in April and May 2003. Parts of the cultural layers, as thick as 1.2 m, discovered during the evaluation, were excavated. Several chronological layers were observed as well as stone packings and pits within the cultural layers. The layers have been built up both deliberately in connection with construction work and through manuring. The finds mainly consisted of burnt and unburnt bone and a few pottery shards. Two pits and a stone packing were dated to the Late Vendel Period/Early Viking Age.
In addition, approx. ten settlement features were excavated, such as pits, hearths and post holes. One of the pits may have been used as a forge. The finds in these features consisted of pottery, burnt clay, slag, burnt and unburnt bones, and an iron knife found in one of the pits. This pit was dated to c. 450-610 AD.

Purpose:

The information in the purpose is translated from the archaeological report:
The overall aim of the excavation was to date, document and interpret the discovered features and to relate them to a culture-historical context.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
Riksantikvarieämbetet, UV Öst, har utfört en arkeologisk slutundersökning inom Kv Skålsvampen i Smedby, f d St Johannes socken, Norrköpings stad och kommun, Östergötland. Anledningen var att Norrköpings kommun planerar för en gång- och cykelväg mellan Brånnestad och Rambodal. Vid en tidigare förundersökning konstaterades att det fanns förhistoriska boplatslämningar längs den planerade vägen.
Slutundersökningen utfördes i april och maj år 2003. Vid undersökningen undersöktes delar av de mycket kraftiga kulturlagren som upptäcktes vid förundersökningen. Lagren var flerskiktade och sammanlagt upp till 1,20 meter tjocka. Flera tidsskeden kunde urskiljas och i lagren fanns dessutom flera olika konstruktioner i form av stenpackningar och nedgrävningar. Lagren har tillkommit genom olika utfyllnader, genom planeringslager för bebyggelse samt genom gödsling av åkermarken. Fynden i lagren och anläggningarna bestod främst av obrända och brända ben samt några enstaka keramikskärvor. Två gropar och en stenpackning daterades till sen vendeltid/tidig vikingatid.
Förutom området med kulturlager undersöktes ett tiotal boplatsrelaterade anläggningar i form av gropar, härdar, och stolphål. En av groparna har troligen fungerat som en smidesässja. Fynden i dessa anläggningar bestod av keramik, bränd lera, slagg, obrända och brända ben samt i en grop även en järnkniv med tången bevarad. Träkol från gropen med kniven daterades till övergången mellan folkvandringstid och vendeltid, ca 450-610 e Kr (Cal 1 sigma).

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Det övergripande syftet med slutundersökningen var att datera, dokumentera och tolka de påträffade anläggningarna samt att sätta in dessa i sitt kulturhistoriska sammanhang.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: Kulturlager och smidesspår vid Smedbygravfältet - Gång- och cykelväg mellan Brånnestad och Rambodal
Keywords: Iron Age; järnålder; HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi